Boundary element analysis of interaction bi-material interface crack with inclusions - Chen, Bryan Jun Wei (Nanyang Technological University, 2024)
This project aims to analyse the interactions between a circular inclusion and an interfacial crack within a bi-material plate of negligible thickness. This study will be utilizing the mathematical technique of Boundary Element Method to compute the stress intensity factor of the crack tips by the means of the Multidomain BEM to divide the region of interest into multiple sub-regions, and the Quarter Point Element to allow for accurate analyse at the crack tip. The parameters that will be explored are the dimensionless distance between the interfacial crack and the centre of circular inclusion, the angle of the distance, as well the various combination of stiffness between the three materials. The conclusion includes how the parameters can be manipulated to induce either an enhancement or shielding effect on the stress intensity factor of the interfacial crack.